Fecundity, Longevity, and Host Finding of Three Parasitoid Species of Liriomyza sativae - HERLINDA, SITI; JAYA, AGUSMAN; PUJIASTUTI, YULIA; RAUF, AUNU (HAYATI Journal of Biosciences, 2009)
Liriomyza sativae is a polyphagous agromyzid leafminer and it has invaded large part of world, i.e Hemiptarsenus varicornis, Gronotoma micromorpha, and Opius dissitus. This research were conducted to investigate progeny, immature development period, longevity of female parasitoids of L. sativae, and to study female parasitoid behaviour in host finding. Host finding behaviour was observed by examining their visit frequency to the leaves that mined by leafminer larvae and healthy leaves. Results showed that H. varicornis produced more progenies (10.70 + 2.58 progenies/female), but not significantly different (P < 0.05) from progenies produced by G. micromorpha (9.90 + 3.81 progenies/female) and O. dissitus (9.60 + 3.31 progenies/female). The immature development period of G. micromorpha (25.65 + 0.38 days) was found to be longer than H. varicornis (16.14 Ã‚Â± 1.20 days) and O. dissitus (14.03 + 0.22 days). Significant different (P = 0.1014) of adult longevity was not found among H. varicornis (9.22 + 2.48 days), G. micromorpha (7.25 + 1.34 days), and O. dissitus (8.74 + 2.18 days). Our analyses also indicated that G. micromorpha and O. dissitus found their hosts based on the larvae mining, however, H. varicornis performed it randomly. Based on the number of progeny and longevity of adult female, all parasitoids tested may have a potential as biological control agents of leafminer, L. sativae. Key words: fecundity, longevity, behavior, Hemiptarsenus, Gronotoma, Opius, Liriomyza sativae